Dibattere a scuola: scegliere il proprio percorso educativo - De Conti, Manuele (Studi sulla Formazione/Open Journal of Education, 2013)
Using debate as an effective educational tool means choosing a suitable debate format for accomplishing the pedagogical aims we have in mind. Thus, the aim of this paper is to understand how each debate format relates to the competen- cies it promotes. It is only through knowing how competencies are stimulated by specific rules of debate formats that we are able to make a reasoned and ef- fective choice.